Diseases of blood vessels. Issue 6 (June 2018) - Carey, Francis A.; Sheppard, Mary N.
Abstract: Cardiovascular disease is the number one worldwide killer of men and women. Atherosclerosis is characterized by deposition of lipids in arterial walls and is responsible for a wide spectrum of end-organ damage. Inflammation of the blood vessel wall (vasculitis) can occur as a secondary process in association with another disease or exposure, or as a primary idiopathic process. The primary vasculitides have individual patterns of vascular involvement and histopathological characteristics that influence their clinical features, severity, and management.